Results of VERTIS SU extension study: safety and efficacy of ertugliflozin treatment over 104 weeks compared to glimepiride in patients with type 2 diabetes mellitus inadequately controlled on metformin. (3rd August 2019) - Hollander, Priscilla; Hill, Julie; Johnson, Jeremy; Wei Jiang, Zhi; Golm, Gregory; Huyck, Susan; Terra, Steven G.; Mancuso, James P.; Engel, Samuel S.; Lauring, Brett; Liu, Jie
Abstract: Objective: To assess the safety and efficacy of ertugliflozin over 104 weeks in patients with type 2 diabetes mellitus (T2DM) inadequately controlled on metformin. Methods: In this double-blind, multicenter, randomized, phase III study (VERTIS SU; NCT01999218), adults with T2DM and glycated hemoglobin (HbA1c) 7.0–9.0% on metformin ≥1500 mg/day received ertugliflozin 5 mg or 15 mg, or glimepiride. The primary efficacy time point was Week 52; double-blinded treatment continued until Week 104. Results: Baseline characteristics of randomized, treated patients ( n  = 1315) were similar across groups (mean age 58.2 years, HbA1c 7.8%); 76.4% completed the study; 61.6% completed on study medication. Mean glimepiride dose at 104 weeks was 3.5 mg/day. At Week 104, least squares mean change from baseline in HbA1c (95% confidence intervals) were −0.3% (−0.4, −0.2), −0.4% (−0.5, −0.3) and −0.4% (−0.5, −0.3) for ertugliflozin 5 mg, 15 mg, and glimepiride, respectively. Ertugliflozin provided sustained reductions in body weight and systolic blood pressure (SBP) over 104 weeks. The incidence of adverse events (AEs) and serious AEs was similar across groups. The incidence of symptomatic hypoglycemia was 3.8%, 6.4% and 22.1% in the ertugliflozin 5 mg, 15 mg, and glimepiride groups, respectively. Genital mycotic infections were reported in 5.3%, 2.6% and 0% of men, respectively, and 9.2%, 12.3% and 1.4% of women, respectively. The incidence of urinary tract infection and hypovolemia AEs was similar across groups. Conclusions: Ertugliflozin was well tolerated and provided clinically meaningful glycemic control and durable reductions in body weight and SBP over 104 weeks. Trial registration: ClinicalTrials.gov identifier: NCT01999218.